Characterization and Salt Response in Recurrent Halotolerant Exiguobacterium sp. SH31 Isolated From Sediments of Salar de Huasco, Chilean Altiplano - Remonsellez, Francisco; Castro-Severyn, Juan; Pardo-Esté, Coral; Aguilar, Pablo; Fortt, Jonathan; Salinas, Cesar; Barahona, Sergio; León, Joice; Fuentes, Bárbara; Areche, Carlos; Hernández, Klaudia L.; Aguayo, Daniel; et al. (Frontiers in Microbiology, 2018)
Poly-extremophiles microorganisms have the capacity to inhabit hostile environments and can survive several adverse conditions that include as variations in temperature, pH and salinity, high levels UV light and atmospheric pressure, and even the presence of toxic compounds and the formation of reactive oxygen species (ROS). A halotolerant Exiguobacterium strain was isolated from Salar de Huasco (Chilean Altiplano), a well-known shallow lake area with variable salinity levels, little human intervention and extreme environmental conditions, which makes it ideal for the study of resistant mechanisms and the evolution of adaptations. This bacterial genus has not been extensively studied, although its cosmopolitan location indicate it has high levels of plasticity and adaptive capacity. However, to date there are no studies regarding the tolerance and resistance to salinity and osmotic pressure. We set out to characterize the Exiguobacterium sp. SH31 strain and describe its phenotypical and genotypical response to osmotic stress. In this context, as a first step to characterize the response to the SH31 strain to salinity and to establish the bases for a molecular study, we proposed to compare its response under three salt conditions (0, 25 and 50 g/l NaCl). Using different physiology, genomic and transcriptomic approaches, we determined that the bacterium is able to grow properly in a NaCl concentration of up to 50 g/l, however, the best growth rate was observed at 25 g/l. Although the presence of flagella is not affected by salinity, motility was diminished at 25 g/l NaCl and abolished at 50 g/l. Biofilm formation was induced proportionally with increases in salinity, which was expected. These phenotypic results correlated with the expression of related genes: fliG and fliS (Motility); opuBA and putP (transport); glnA, proC, gltA and gbsA (compatible solutes); ywqC, bdlA, luxS y pgaC (biofilm and stress response); and therefore, we conclude that this strain effectively modifies gene expression and physiology in a differential manner when faced with different concentrations of NaCl and these modifications aid survival.